Fundamentals of ground radar for air traffic control engineers and technicians - Bouwman, Ronald (SciTech Pub., 2009)
The following topics in this book are discussed: radar history; secondary radar systems; air traffic control; microwave transmission lines and cavities; radar synchronizers; radar transmitters; radar receivers; moving target indicator; Doppler effect; moving target detector; and radar displays.
Keywords: Radar air traffic control systems.; Radar in aeronautics.; Radar -- History.; Radar -- Equipment and supplies.; elektronické knihy; electronic books